PTU-059 EMR for early barrett's neoplasia: 15-years of experience from a UK tertiary referral centre. (June 2019) - White, JR; Ortiz-Fernández-Sordo, J; Santiago-García, J; Reddiar, D; De Caestecker, J; Cole, A; Kaye, P; Ragunath, K
Abstract : Introduction: Endoscopic mucosal resection (EMR) is a widely used therapy for visible dysplastic lesions associated with Barrett's oesophagus (BO) and intramucosal adenocarcinoma (IMC). This study evaluates the efficacy and safety of a single high-volume UK tertiary centre with 15-years experience. Methods: A retrospective review was conducted of patients referred to Nottingham University Hospital between 2004–2019 for EMR with dysplastic BO visible lesions or IMC. The main outcomes were endoscopic resection success rates, long-term recurrence rates, complications during the treatment phase, surgery rates, median follow up prior to discharge from tertiary centre and tumour related deaths. Results: A total of 309 lesions were resected in 212 patients, median age was 68.1±9.4 years, the male: female ratio was 5:1. Median BO length was C2(IQR:6) M4(IQR6) and 76.2% of lesions were at the 12 to 6 o'clock position. The most common lesion was Paris IIa (63.4%) and the median size was 10 mm (3–70). Most procedures were done under intravenous sedation as a day-case with the ligate and cut technique (93.2%) and the Duette® multi-band mucosectomy device (88%). APC was used in addition to EMR in 5.4% of cases. Complete resection rates were 95.5%. Prophylactic measures to prevent bleeding were undertaken in 11.3%. Significant complications requiring admission and further treatment was 3.8%: bleeding (2.3%) and perforation (0.3%) with a median length of stay of 1 day (1-8). Stricture rates were 2.6% requiring a median of 1 (IQR:1.75) dilatation. The most commonly resected histological grade was IMC (48.1%), high grade dysplasia (37%) and low grade dysplasia (6.5%). The majority of tumours were stage T1a (86.7%). 22% of patients with confirmed adenocarcinoma had an indication for surgery and over half of these underwent surgery. Post EMR 72.5% had additional therapy for the remaining BO. After a median follow up of 32 months (IQR 43.6) metachronous lesions developed in 10.7% of patients. 95% of these were successfully treated with endoscopic or surgical therapy. The survival rate over the study period was 85.7%, with cause of death attributed to unrelated disease (11.3%) and oesophageal adenocarcinoma (2.8%). Conclusions: This real-world data demonstrates that EMR is a minimally invasive, safe and effective treatment for Barrett's neoplasia that can be delivered in a day-case setting. It allows accurate local staging with the option of surgery for locally advanced disease.